Tawhid and Qur’anic Interpretation in Early 20th-Century Minangkabau: A Philological-Theological Study of Abdul Latif Syakur’s al-Tawḥīd (1882–1963) - Ridhoul Wahidi; Benny Afwadzi; Syafril; Riki Rahman (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
The Islamic reform movement in early 20th-century Minangkabau, West Sumatra, evolved through three phases. The first phase involved intellectual engagement, followed by military conflict, and later, modernization through education. During the third phase, scholarly production increased significantly. However, reformist literature predominantly concentrated on debates about tariqa (religious order) and fiqh (jurisprudence). Substantive discourse on tawhid (oneness of God) was absent, which forms the foundation of aqidah (creed). This study explores Abdul Latif Syakur’s al-Tawhid manuscript (1882–1963) to explore this underexamined aspect of Islamic theological discourse. Employing an integrative qualitative approach (philological-theological and historical analysis), the research explores three aspects: (1) Syakur’s construct of integrative tawhid, which synthesizes rubūbiyyah (lordship), ulūhiyyah (godship), and asmā’ wa ṣifāt (divine names and attributes); (2) his critique of shirk (associating partners with God) in both its jahiliyyah (pagan-ritualistic) and modern (secular-materialistic) forms; and (3) the role of ikhlas (sincere devotion) as a bridge between tawhidand social praxis. The findings show Syakur presents a non-polemical approach, integrating Minangkabau's local values (adat basandi syarak, or Sharia-based tradition) with Islamic doctrine. He also critiques the tendency to reduce tawhid to ritual formalism or a strict separation between religion and state. His concept of modern shirk provides valuable insights into current challenges, such as materialism and environmental issues. By integrating education and literacy at an institution informally known as Surau Si Camin, Syakur contributed to a holistic reform that emphasized the unity of aqidah, ethics, and social responsibility. This study affirms the relevance of integrative tawhid as a framework for conflict resolution and interfaith dialogue in pluralistic societies while revitalizing the intellectual legacy of Islam in the Nusantara region (the Malay-Indonesian archipelago).